2004
DOI: 10.1128/aac.48.3.867-872.2004
|View full text |Cite
|
Sign up to set email alerts
|

Geldanamycin, a Ligand of Heat Shock Protein 90, Inhibits the Replication of Herpes Simplex Virus Type 1 In Vitro

Abstract: Geldanamycin (GA) is an antibiotic targeting the ADP/ATP binding site of heat shock protein 90 (Hsp90).In screening for anti-herpes simplex virus type 1 (HSV-1) candidates, we found GA active against HSV-1. HSV-1 replication in vitro was significantly inhibited by GA with an 50% inhibitory concentration of 0.093 M and a concentration that inhibited cellular growth 50% in comparison with the results seen with untreated controls of 350 M. The therapeutic index of GA was over 3,700 (comparable to the results seen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
77
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(79 citation statements)
references
References 37 publications
2
77
0
Order By: Relevance
“…Geldanamycin is a naturally occurring molecule that specifically binds the ADP/ATP-binding cleft of Hsp90 and destabilizes its interaction with client proteins. We have confirmed the results of Li et al showing that geldanamycin inhibits HSV-1 replication in tissue culture (13). Our results suggest that the viral polymerase may be a client protein of the Hsp90 chaperone machine and that geldanamycin inhibits HSV DNA replication by blocking Hsp90-polymerase interactions required for nuclear targeting.…”
Section: Discussionsupporting
confidence: 81%
“…Geldanamycin is a naturally occurring molecule that specifically binds the ADP/ATP-binding cleft of Hsp90 and destabilizes its interaction with client proteins. We have confirmed the results of Li et al showing that geldanamycin inhibits HSV-1 replication in tissue culture (13). Our results suggest that the viral polymerase may be a client protein of the Hsp90 chaperone machine and that geldanamycin inhibits HSV DNA replication by blocking Hsp90-polymerase interactions required for nuclear targeting.…”
Section: Discussionsupporting
confidence: 81%
“…Of particular interest is the role of Hsp90. It has been shown that geldanamycin, a specific inhibitor of Hsp90 (34), inhibits the replication of HSV-1 in cell culture (25); therefore, Hsp90 and at least one of its downstream targets are necessary for HSV-1 replication. Geldanamycin also inhibits the replication of (25).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that geldanamycin, a specific inhibitor of Hsp90 (34), inhibits the replication of HSV-1 in cell culture (25); therefore, Hsp90 and at least one of its downstream targets are necessary for HSV-1 replication. Geldanamycin also inhibits the replication of (25). Because Hsp90 is critical for the replication of many viruses and is an important component of the cellular response to stress, which induces HSV-1 reactivation from latency, Hsp90 is a potentially important factor in HSV-1 reactivation.…”
Section: Discussionmentioning
confidence: 99%
“…An antibiotic geldanamycin (GA), which was initially characterized as an anticancer agent, has been reported to exhibit broadspectrum antiviral activity in vitro against several viruses by targeting the ADP/ATP binding site of Hsp90 [21]. The target viruses include herpes simplex virus type-1 (HSV-1) [10], severe acute respiratory syndrome corona virus, vaccinia virus [23], influenza virus, vesicular stomatitis virus [22], hepatitis C virus [24] and ebola virus [11].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous Hsp90 inhibitors, identified as anticancer agents such as radicicol, geldanamycin (GA), and GA derivatives, block Hsp90 activity by binding to the N-terminal ATP pocket of the protein and inhibiting ATPase activity [9]. Geldanamycin was shown to be active against replication of a range of viruses, including herpes simplex virus type 1 (HSV-1), severe acute respiratory syndrome coronavirus and Zaire EBOV in vitro [10,11].…”
Section: Introductionmentioning
confidence: 99%